Predicting intention to participate in mobile crowdsourcing initiatives : a study of local Kenyan communities - Gatara, Maradona (My University, 2013)
Crowdsourcing is the outsourcing of a job or task to a large group of individuals. Crowdsourcing has emerged from the concepts of Outsourcing, Open Source Software (OSS) Collaboration, Open Innovation, and User Innovation. While Crowdsourcing has provided an innovative way in which work can be outsourced to a large group of people, the advent of Mobile Telephony in Africa has provided a whole new dimension. This is the merging of the concepts of Crowdsourcing and Mobile Telephony, to form Mobile Crowdsourcing. Mobile Crowdsourcing has the potential to contribute significantly to the use of Information Technology (IT) in developing countries by providing a platform that would enable people such as those in peri-urban Kenyan communities, to utilise their mobile handsets to perform a set of mobile-based tasks. Payment for these tasks is made possible through mobile money platforms such as “M-Pesa”. Such innovation could provide a means for social empowerment for many of these unemployed technology users. This study sets forth to examine a set of factors that are likely to predict the “participation intention” of peri-urban Kenyan youths in Mobile Crowdsourcing. Motivational Theory, and the Theory of Reasoned Action (TRA) form the core of the theoretical framework used for this study. The McKnight Model is used as a supporting theory, to examine “trusting beliefs”. In addition, the constructs “perceived credibility”, “social influence” and “community identification” are derived from prior studies that use Socio Cognitive Theory and an extended version of the Technology Acceptance Model (TAM). These also play a supporting role. Using a survey instrument, data was collected from peri-urban youths in four peri-urban communities, and 279 usable responses were obtained for this study. Findings show that “self-development”, “integrity”, and “reputation” are the most significant predictors of “participation intention”. These three variables account for 17% of the variance in “participation intention”. Contrary to suggestions made in prior literature on Crowdsourcing, “monetary compensation” was not found to be a key motivator. This finding will no doubt spark future debate as to the role money plays in Crowdsourcing, especially in Africa. Additional findings show that “attitude” was found to be a strong mediator of the relationship between “technology anxiety” and “participation intention”. Moreover, “community identification” was found to be a full moderator of the relationship between “social influence” and “participation intention”. Findings made uncovered new insights about the perceptions and attitudes of mobile phone users in developing countries. Contributions made to theory and practice are also discussed.
Keywords: Crowdsourcing; mobile telephony; Mobile crowdsourcing; Kenya; Africa; Developing countries